PENGARUH PENERAPAN STRATEGI BERIKAN UANGNYA TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 2 SIJUNJUNG TAHUN PELAJARAN 2012/2013 - Oktaviarla, Zakia; K, Delsi; Harisman, Yulyanti (Pendidikan Matematika, 2013)
The backgraund of the research is the comprehension of the concept is still low on mathematic on grade eight in SMP Negeri 2 Sijunjung. The aim of the research is to know whether the implementation of conceptual comprehension of Give The Money learning stategy is better than conventional. This is an experimental research, by designing random research on the subject. Technique of sampling is grade VIII1 as the experiment class and grade VIII5 as control class. The instrument of the research is final test by using conceptual comprehension and rubrik test analytical. The test is essay. Technique of analysis is t-test. Based on the result of analysis data, it is known that both samples normal and homogen up to 95% accuracy and the result of hypotesis of p-value is 0,018 and the p-value less than 0,05. So this hypotesis of this research is accepted. It can be concluded that conceptual comprehension of mathematic by using Give The Money strategy is better than by using conventional from students grade VIII of SMP Negeri 2 Sijunjung.